2019
DOI: 10.3390/s19132858
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Functionalized Piezoresistive Hydrogel Biosensors for the Detection of Urea

Abstract: Urea is used in a wide variety of industrial applications such as the production of fertilizers. Furthermore, urea as a metabolic product is an important indicator in biomedical diagnostics. For these applications, reliable urea sensors are essential. In this work, we present a novel hydrogel-based biosensor for the detection of urea. The hydrolysis of urea by the enzyme urease leads to an alkaline pH change, which is detected with a pH-sensitive poly(acrylic acid-co-dimethylaminoethyl methacrylate) hydrogel. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 58 publications
0
30
0
2
Order By: Relevance
“…Hydrogels have been used as drug delivery vehicles as they can encapsulate hydrophilic drugs and release them at a controlled rate within the body, through solute diffusion, or matrix swelling or degradation [3]. Researchers have also taken advantage of the ability of hydrogels to swell or shrink in response to external stimuli (e.g., pH, temperature) to develop biosensors for the detection of biomolecules [4,5]. Additionally, their highly porous and hydrated polymer structure mimics the extracellular cellular matrix and renders them highly suitable for in vitro cell culture, and several studies have demonstrated the successful use of hydrogels to encapsulate mammalian cells in a 3D physiological-like environment and develop in vitro models of cell proliferation, migration, and differentiation [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels have been used as drug delivery vehicles as they can encapsulate hydrophilic drugs and release them at a controlled rate within the body, through solute diffusion, or matrix swelling or degradation [3]. Researchers have also taken advantage of the ability of hydrogels to swell or shrink in response to external stimuli (e.g., pH, temperature) to develop biosensors for the detection of biomolecules [4,5]. Additionally, their highly porous and hydrated polymer structure mimics the extracellular cellular matrix and renders them highly suitable for in vitro cell culture, and several studies have demonstrated the successful use of hydrogels to encapsulate mammalian cells in a 3D physiological-like environment and develop in vitro models of cell proliferation, migration, and differentiation [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This review aims to investigate, how hydrogels contribute to improving these parameters. [23] (PEG methacrylate) Dye, protein, Oligonucleotide Fluorescence Covalent, Diels-Alder cycloaddition [50,51] Chitosan Enzymes Chromogenic (indigo) Covalent, amide bond [54] Chitosan, dextran Glucose Electrochemical Electrostatic [76] Responsive Hydrogels Acrylic acid and dimethylaminoethyl methacrylate Urea Piezoresistive pressure sensor Encapsulation [90] Shape-memory DNA film pH, Ag + /cysteine Photonic crystal Hybridization [93] Poly(methyl methacrylate-co-methacrylic acid)…”
Section: Biosensingmentioning
confidence: 99%
“…In fact, an increasing in concentration of urea determined the increase of pH through the hydrogel and altered the 4-MPy SERS response. Erfkamp and co-workers fabricated an enzyme hydrogel-based piezoresistive ammonia sensor based on alkaline pH change sensitive hydrogels [74]. The hydrogels were synthetized using acrylic acid and 2-(dimethylamino)ethyl methacrylate, fixed in the center of a circuit broad and then a pressure sensor chip was put on the top of the gel.…”
Section: Physicochemical Sensormentioning
confidence: 99%